Enhanced Anti-Inflammatory Effects of Silibinin and Capsaicin Combination in Lipopolysaccharide-Induced RAW264.7 Cells by Inhibiting NF-κB and MAPK Activation - Zheng, Yingying; Chen, Jie; Wu, Xiaozheng; Zhang, Xin; Hu, Chunmei; Kang, Yu; Lin, Jing; Li, Jiamin; Huang, Yuechang; Zhang, Xingmin; Li, Chen (Frontiers in Chemistry, 2022)
Silibinin and capsaicin both are natural product molecules with diverse biological activities. In this article, we investigated the anti-inflammatory effects of silibinin combined with capsaicin in lipopolysaccharide (LPS)-induced RAW264.7 cells. The results showed that silibinin combined with capsaicin strongly inhibited LPS-induced nitric oxide (NO), tumor necrosis factor-α (TNF-α), Interleukin-6 (IL-6), and COX-2. Moreover, silibinin combined with capsaicin potently inhibited nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways. The results of the present study indicate that silibinin combined with capsaicin effectively inhibits inflammation.